Desarrollo de alumnos talentosos en la educación superior técnica tecnológica de Ecuador. Caso de estudio: Integración a un concurso académico externo (Experiencias) - Yépez Moreira, Rolando Ismael (2023)
The effects of the memories of the integration of a talented student of the Ecuadorian technological technical higher education in an external academic contest are described. The methodological process is based on the achievement of three phases: the first for the selection and preparation of the student, the second for the development of the contest, and phase three to evaluate the skills acquired by the student after their participation. The experience and learning of the successful participation in the event falls mainly on the strengthening of behavioral competencies related to perseverance to achieve and complete the goals set, effective performance during collaborative work, the development of relationships, effective social and self-recognition as an individual who contributes to a certain social niche and to the productive sector for which he has been trained. The results established the linking of talented students to external competitions as a valid strategy for developing competencies, mainly behavioral, which, for reasons and conditions specific to this type of student, have not been able to be potentiated in the classroom.